SAT1000 - P931

Geometry Level 3

As shown above, from top to bottom, l 1 l_1 , l 2 l_2 , and l 3 l_3 are three parallel lines on the same plane, and the distance from l 1 l_1 to l 2 l_2 is 1 1 , the distance from l 2 l_2 to l 3 l_3 is 2 2 , and point A , B , C A,B,C are on l 1 , l 2 , l 3 l_1, l_2, l_3 respectively.

If A B C \triangle ABC is an equilateral triangle , then find the side length of A B C \triangle ABC .

Let l l denote the side length. Submit 1000 l \lfloor 1000l \rfloor .


Have a look at my problem set: SAT 1000 problems


The answer is 3055.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jul 10, 2020

Let the measure of the angle between A B AB and line l 2 l_2 be θ \theta . Then we have:

{ sin θ = 1 l . . . ( 1 ) sin ( 6 0 θ ) = 2 l . . . ( 2 ) \begin{cases} \sin \theta = \dfrac 1l & ...(1) \\ \sin(60^\circ - \theta) = \dfrac 2l & ...(2) \end{cases}

From ( 2 ) (2) :

3 2 cos θ 1 2 sin θ = 2 l = 2 sin θ As ( 1 ) : sin θ = 1 a 3 2 cos θ = 5 2 sin θ tan θ = 3 5 sin θ = 3 5 2 + 3 = 3 28 ( 1 ) : l = 1 sin θ = 28 3 3.055050463 1000 l = 3055 \begin{aligned} \frac {\sqrt 3}2 \cos \theta - \frac 12 \sin \theta & = \frac 2l = 2 \blue{\sin \theta} & \small \blue{\text{As }(1) : \ \sin \theta = \frac 1a} \\ \frac {\sqrt 3}2 \cos \theta & = \frac 52 \sin \theta \\ \tan \theta & = \frac {\sqrt 3}5 \\ \implies \sin \theta & = \frac {\sqrt 3}{\sqrt{5^2+3}} = \sqrt{\frac 3{28}} \\ (1): \quad \implies l & = \frac 1{\sin \theta} = \sqrt{\frac {28}3} \approx 3.055050463 \\ \implies \lfloor 1000l \rfloor & = \boxed{3055} \end{aligned}

Place the figure onto the xy-plane. Let the difference between the x-coordinates of A and B be a a and let the difference between the x-coordinates of B and C be b b . It follows that a 2 + 1 = l 2 a^2 + 1 = l^2 , b 2 + 4 = l 2 b^2 + 4 = l^2 , and ( a b ) 2 + 9 = l 2 (a-b)^2 + 9 = l^2 .

Using the first two equations, we conclude that a 2 = b 2 + 3 a^{2}=b^{2}+3 . Substituting this into the third equation and expanding yields 2 b 2 2 b b 2 + 3 + 12 = b 2 + 4 2b^{2}-2b\sqrt{b^{2}+3}+12=b^{2}+4 which is equivalent to 3 b 4 4 b 2 64 = 0 3b^{4}-4b^{2}-64=0 for positive b b . Applying the quadratic formula and solving for b b yields b = 4 3 3 b = \frac{4\sqrt{3}}{3} . Substituting this value for b b into b 2 + 4 = l 2 b^2 + 4 = l^2 gives us l = 28 3 l = \sqrt{\frac{28}{3}} . 1000 l = 3055 \lfloor 1000l \rfloor = \boxed{3055} .

Jeff Giff
Jul 10, 2020

See this :) what a coincidence!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...